THE IMPLEMENTATION OF FACILITIES AND INFRASTRUCTURE MANAGEMENT AT MIS HIDAYATUL MUBTADIIN MUKOMUKO IN IMPROVING THE QUALITY OF MADRASAH EDUCATION - Masdiana, Masdiana; Puspitasari, Tuti; Desiono, Maula (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2022)
The quality of national education which is reflected in the competence of graduates of educational units is influenced by various components such as process, content, educators and education personnel, facilities and infrastructure, management, financing, and educational assessment which can be described in the constellation of education quality. The realization of a quality education process is influenced by the performance of educators and education staff, the quality and quantity of facilities and infrastructure, the quality of management, the availability of funds, and a valid, objective, and firm assessment system. Therefore, the realization of quality national education must be supported by educational content and processes which meet standards, educators and education personnel who meet standards of academic qualifications and competencies in order to perform optimally, as well as facilities and infrastructure, management, and financing which meet standards. The management of facilities and infrastructure is also in accordance with the existing management procedures of all existing facilities and infrastructure in the institution, especially MIS Hidayatul Mubtadiin Mukomuko, facilities, and infrastructure are also one of the initial requirements in improving the quality of education so that it can produce outputs which are able to compete with other schools in Mukomuko Regency.Â